Increasing disparities in the proportions of active treatment and 5-year overall survival over time by age groups among older patients with gastric cancer in Korea - Zhang, Hyun-Soo; Choi, Dong-Woo; Kim, Han Sang; Kang, Hye Jung; Jhang, Hoyol; Jeong, Wonjeong; Nam, Chung Mo; Park, Sohee (Frontiers in Public Health, 2023)
Purpose: As older patients with gastric cancer increase in Korea, no consensus indicative of anti-cancer treatment exists for the oldest old (age 85+). We investigated potential disparities in the proportion of surgery-including active treatment and the degree of survival improvement over time by age groups, and whether heterogeneity exists in the protective effect of time period on overall survival (OS) by age at diagnosis clusters. Materials and Methods: A nationwide cohort (N=63,975) of older patients with gastric cancer (age at diagnosis 70+) in 2005-2012 were followed until the end of 2018. Patients were categorized into four time period groups by their year of diagnosis. Cancer treatment patterns and 5-year OS were analyzed accordingly, and a random coefficients Cox model with random intercepts and random slopes of time period by age at diagnosis clusters was employed. Results: The mean age of patients was 76.4, and 60.4% were males. Most patients had 0-1 comorbidities (73.3%) and low-risk frailty scores (74.2%). Roughly two-thirds of patients received some form of anti-cancer treatment (62.4%), and while the number of comorbidities and the proportion of high-risk frailty scores trended toward an increase, the proportion of patients receiving anti-cancer treatment increased from 58% in 2005-2006 to 69.6% in 2011-2012. The proportion of surgery-including active treatment increased to over 70% in the 70-74 years old group, while stagnating at 10% in the 90+ years old group. Differences in the slope of 5-year OS improvement resulted in a widening survival gap between the old (age 70-84) and the oldest old. The protective effect of time period on OS hazard in the oldest old was not monotonically reduced with increasing “chronological” age but varied quite randomly, especially among female patients. Conclusion: Our study showed no upper age limit in terms of benefiting from the advances in the detection and treatment of gastric cancer over time. Thus, “functional” age rather than “chronological” age should be the criterion for anti-cancer screening and treatment, and actual implementation of proven treatments in the oldest old patients to reduce their non-compliance with treatment in clinical practice is needed to improve gastric cancer survival for all.